Hard-coupling water and power system models increases the complementarity of renewable energy sources. (1st September 2022) - Koh, Rachel; Kern, Jordan; Galelli, Stefano
Abstract: The soft (one-way) coupling of water and power system models is the dominant approach for studying the impact of water availability on grid performance. Yet, such approach does not explicitly capture key dynamic interdependencies between the state of the grid and the operational decisions made at the water system level. Here, we address this gap and introduce a novel numerical modelling framework that hard-couples a multi-reservoir system model and a power system model. The framework captures two-way feedback mechanisms and thereby enables operational decisions to be made contingent upon the states of both the water and energy system. We evaluate the framework on a real-world case study based on the Cambodian grid. In light of the country's plan to further decarbonize its grid, we tested the framework on three grid configurations—the as-is grid, and the grid with two different levels of installed solar capacity. Simulation experiments were run with and without feedback, while uncertainty in external forcings was explored through 1, 000 stochastic time series of streamflow, solar production, and load. As demonstrated in our results, hard-coupling the water and energy systems reduces operating costs and CO 2 emissions while increasing the integration of renewables. Under favourable conditions (large reservoir inflow and low electricity demand), the system experienced a 44% saving in annual operating costs and 53% reduction of CO 2 emissions. A spatio-temporal analysis on the reservoir operations and transmission line usage reveals that the timing of the monsoon and interconnections between individual grid components also play significant roles in influencing the system's responses to the hard coupling. Overall, simulation frameworks like this provide a modelling framework for testing management and planning solutions aimed to improve the performance of water-energy systems. Highlights: A novel hard-coupling modelling framework for water-energy systems. We model two-way feedbacks between hydropower reservoirs and power grid. Hard-coupling can be applied on large-scale grids and cascade reservoirs. Model flexibility improves integration of renewables in the grid. Other benefits include reduced power production costs and CO2 emissions.